Design, Considerations, and Implementation of a Solar-Powered Smart Street Lighting System with Integrated CCTV and IoT-Based Monitoring - Muhammad Rizani Rusli; Rachma Prilian Eviningsih; Lucky Pradigta Setiya Raharja; Luki Septya Mahendra; Achmat Ridwan Nudin; Naufal Fadhlirahman Dheningrat; Akmal Fikri; Mentari Putri Jati (Universitas Teknologi Yogyakarta, Yogyakarta, Indonesia, 2026)
This study presents the design, implementation, and short-term experimental validation of a standalone solar-powered smart street lighting system integrating LED illumination, CCTV surveillance, and Internet of Things (IoT)-based real-time monitoring within a single pole-mounted platform. Load profiling identified a total energy demand of 1176 Wh/day, which increased to 1529 Wh/day after applying a 30% design margin. These requirements guided the selection of a 460 Wp monocrystalline photovoltaic module, a 40 A maximum power point tracking charge controller, and a 12.8 V, 150 Ah LiFePO₄ battery. Laboratory testing demonstrated the expected bulk/MPPT, boost, and float charging stages, while accelerated battery testing at 0.27C measured a capacity of 151 Ah. During five consecutive days of field testing under sunny to partly cloudy conditions, the post-charging state of charge (SOC) ranged from 90.0% to 97.2%, while the next-morning SOC ranged from 58.6% to 68.4%. The average nighttime SOC reduction was 32.8%, with a range of 25.1% to 37.3%. The IoT platform provided real-time monitoring of photovoltaic generation, battery condition, and load operation, while maintaining communication availability above 99% during the observation period. These results demonstrate short-term autonomous operation and technical feasibility under the observed field conditions. Longer seasonal testing and a complete life-cycle economic assessment remain necessary to evaluate long-term reliability and financial feasibility.